Smart surveillance using PDA - Abdurahaman Muftah, Basem Mustafa (2006)
The aim of this research is to develop a fast and reliable surveillance system based on a personal digital assistant (PDA) device. This is to extend the capability of the device to detect moving objects which is already available in personal computers. Secondly, to compare the performance between Background subtraction (BS) and Temporal Frame Differencing (TFD) techniques for PDA platform as to which is more suitable. This project is designed for Pocket PC devices (windows Mobile 2003 SE or windows CE 4.2) meant for indoor use only. The system is capable to operate at 5 frames per second. The entire surveillance program has been developed and programmed using Embedded Visual C++ taking the advantage of the built-in camera. In order to reduce noise and to prepare frames for the moving object detection part, each frame is first converted to a gray-scale representation and then smoothed using a Gaussian low pass filter. Two moving object detection schemes i.e., BS and TFD have been analyzed. TFD is done by taking the difference between the current frame and the previous frame. On the other hand BS is accomplished by taking the difference between subsequence frame and the background frame. The background frame is updated by using Infinite Impulse Response (IIR) filter so that the background frame is adapted to the varying illuminate conditions and geometry settings. In order to reduce the effect of noise pixels resulting from frame differencing morphological filters erosion and dilation are applied. In this work, it has been found that TFD technique is more suitable for motion detection purpose than the BS in term of speed. On average TFD is approximately 170 ms faster than the BS technique